Assessment of heavy metals removal using bioflocculant produced by Bacillus subtilis UPMB10 - Wang, Yang (2023)
Due to urbanization, industrialization, and agricultural activities, heavy metal pollution has become one of the most significant environmental issues. Heavy metals are highly soluble in the aquatic environment, which makes it possible for them to bio-accumulate and magnify in living organisms, leading to health issues. Therefore, metal-contaminated wastewater must be treated before being released into the environment. Conventional methods for metal removal are expensive and generate secondary pollution. Bioflocculants have received more attention as they can be an alternative solution to remove heavy metals because of their safety and biodegradability. The heavy metal removal efficiency of bioflocculant produced by Bacillus subtilis UPMB10 for three metals, zinc (Zn), arsenic (As) and lead (Pb) in single and mixed synthetic metal solutions and exmining lake water collected from Kg. Gajah, Perak was studied. One-factor-ata- time (OFAT) analysis was used to assess the influence of bioflocculant dosage, initial pH, and initial metal concentration on the efficiency of heavy metal removal. The concentration of metals before and after treatment was measured by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The results showed that at 5 mg/L of metal concentration and pH 7, the removal efficiency of Zn and As significantly increased with an increment in bioflocculant dosage from 5% (v/v) to 20% (v/v) (p ≤ 0.05). However, the removal efficiency of Pb significantly declined with increased bioflocculant dosages (p ≤ 0.05). In the 5 mg/L of metal concentration with the bioflocculant dosages of 5% (v/v), heavy metals (Zn, As, Pb) showed the highest removal efficiency at pH 7 than at pH 4 and 9 with significant difference (p ≤ 0.05). With bioflocculant dosages of 5% (v/v) at pH 7, the efficiency to remove heavy metals (Zn, As, and Pb) significantly increased as the heavy metal concentration increased from 1 to 60 mg/L (p ≤ 0.05). Under all conditions, Zn and As were more effectively removed from mixed metal solution than from single metal solution. Conversely, Pb was more effectively removed from single metal solution. In this study, the highest removal efficiencies for Zn (66.40%) and As (45.45%) were found to occur in a mixed metal solution of 60 mg/L with a bioflocculant dosage of 5% (v/v) and pH 7. Meanwhile, the highest Pb removal efficiency (98.74%) was found in a single metal solution of 60 mg/L with a bioflocculant dosage of 5% (v/v) and pH 7. On the other hand, heavy metals (Zn, As, Pb) in the ex-mining lake water samples were effectively removed at 56.4%, 64.0%, and 78.0% with bioflocculant dosages of 20% (v/v), respectively. Overall, bioflocculant produced by B. subtilis UPMB10 has the potential to remove Zn, As, and Pb, and could be used as an effective bioflocculant agent for environmental remediation of heavy metals